Results of postoperative radiotherapy in the treatment of 29 uterine sarcoma patients - (:unkn) unknown (PENSIERO SCIENTIFICO EDITOR, 2003)
Aims and background: The objective of this study was to evaluate the results of surgery combined with postoperative radiotherapy (FIT) in patients with uterine sarcoma in order to describe the patterns of relapse and to define prognostic factors. Methods: We report on 29 patients with uterine sarcoma (US) treated from 1980 to 1995; 18 patients with primary tumors were treated with surgery and adjuvant irradiation, while 11 patients with local recurrences (LR) after previous surgical resection received only radiotherapy. We evaluated the influence of stage, histology, grade, menopausal status, total radiation dose and brachytherapy on survival. Histological diagnosis was leiomyosarcoma in 13 patients (44.8%), endometrial stromal sarcoma in 10 patients (34.5%), and mixed mesodermal tumors in six patients (20.7%). Fifteen patients presented with stage I-II disease, three with stage III, and II with local recurrences. External pelvic RT was administered to all patients, in five patients combined with brachytherapy. The mean total dose was 54 Gy (SE 1.78). Univariate and multivariate analyses were carried out. Results: Overall survival (OS) for the stage I-III group was 61.1% at two years and 33.3% at five years (median 29 months, SE 13.79). Disease-free survival (DFS) was 55.6% at two years and 33.3% at five years. Median DFS was 26 months (SE 14.85). In LR cases, median OS was only 10 months (SE 4.5). Multivariate analysis demonstrated that stage was the only prognostic factor after RT for US. Conclusions: These data suggest that postoperative and/or salvage FIT has a questionable impact on disease-free and overall survival because of the lack of homogeneity of stages in the series reported in the literature; it has, however, acceptable late side effects. Prospective multicenter trials including a statistically evaluable number of patients are necessary to further clarify the role of RT treatment programs for US.
Keywords: local recurrence; radiotherapy; uterine sarcoma; MIXED MULLERIAN TUMORS; PROGNOSTIC FACTORS; RADIATION-THERAPY; UTERUS; MANAGEMENT; SURVIVAL; CORPUS